The Effect of Enforcing Accounting Accountability and Strategy Implementation on Corporate Performance - Indra Kurniawan; Irwan Moridu; Denisa Denisa (Lembaga Pengembangan Kinerja Dosen, 2024)
This study investigates the impact of enforcing accounting accountability and implementing strategic measures on corporate performance. By examining the correlation between these factors, the research aims to elucidate how adherence to accounting standards and effective strategy execution contribute to overall company success. Through empirical analysis and case studies, the study evaluates the extent to which accountability in accounting practices and strategic planning influence key performance indicators such as profitability, efficiency, and sustainability. The findings provide valuable insights for organizations seeking to optimize their operational and financial performance through enhanced accountability and strategic decision-making processes.